Bahasa Sunda Gen Millenial dan Gen Z di Aplikasi Tiktok - Dzulfikar, Haidar Ali; Afriani, Annisa Dwi; Meilani, Nur; Sundari, Miranda; Mubarok, Acep Nurul; Wulandari, Eva (Jurnal Bahasa dan Sastra, 2026)
This study aims to describe the use of the Sundanese language by the Millennial Generation and Generation Z on the TikTok application, particularly in the form of code-mixing in everyday conversations; to identify patterns of phonological changes that emerge in words adapted from Indonesian and English into Sundanese; and to distinguish the characteristic features of language use across generations. The research employs a qualitative method, with data collected from several sentences quoted from TikTok videos uploaded by selected accounts, namely @susylawaty_, @susybarokahkammal, and @anisasitiaisyah883 as representatives of the Millennial Generation, and @elsanuraisyah09, @indahcantiii01, and @astridjuwitaaa as representatives of Generation Z. The findings indicate that the Millennial Generation tends to use Sundanese while largely maintaining traditional sentence structures, despite the presence of some loanwords. In contrast, Generation Z demonstrates a more flexible and expressive use of Sundanese, characterized by dominant code-mixing, frequent use of global terms, and more liberal phonological adaptations. These findings suggest that the use of the Sundanese language among contemporary generations continues to evolve through speakers’ creativity and is strongly influenced by the digital culture that flourishes on social media platforms.